2021
DOI: 10.4314/njt.v40i4.6
|View full text |Cite
|
Sign up to set email alerts
|

Production and characterization of biodiesel from mango seed oil (MSO)

Abstract: Biodiesel in the past, was once considered a fringe fuel. However today, the production and consumption of this fuel has grown as a sustainable and much more eco-friendly alternative to the Conventional diesel (Petroleum diesel), for diesel engines; if not in pure form, it will be in blends of different ratios, or as a fuel additive, to improve engine performance and ensure longevity. In this research, oil from Mango (Mangifera indica) seed was extracted through Soxhlet solvent process, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…Table 2 presents details on the yield of oil derived from mango seeds via the solvent-based extraction method. Specifically, the yield of 16.50% obtained is in good agreement with 15-17% reported in the literature (Okonkwo and Omenihu, 2021). Oils with good potentials for upgrade to fuels or direct energy applications must exhibit certain physicochemical properties.…”
Section: Characterization Resultssupporting
confidence: 88%
“…Table 2 presents details on the yield of oil derived from mango seeds via the solvent-based extraction method. Specifically, the yield of 16.50% obtained is in good agreement with 15-17% reported in the literature (Okonkwo and Omenihu, 2021). Oils with good potentials for upgrade to fuels or direct energy applications must exhibit certain physicochemical properties.…”
Section: Characterization Resultssupporting
confidence: 88%
“…Conventional management of these wastes also has economic and environmental impacts unless there is integration between different waste‐to‐energy conversion and other valorization techniques. Various research findings confirmed that anaerobic digestion of mango byproducts contributes to the production of biogas, 4,21 bioethanol, 22 biodiesel, 23 bio‐briquettes, 8,24 and oil extraction 15,25 . Besides addressing energy insecurity and reducing emissions, it also generates higher economic benefits by reducing costs associated with purchasing virgin raw materials in food processing, nutraceutical, and pharmaceutical industries, and by creating new employment opportunities 1,26 .…”
Section: Introductionmentioning
confidence: 88%
“…The waste mange seeds are collected from local waste disposal systems and local mango processing industries in Andhra Pradesh, India. Then, the collected seeds are cleaned with the help of water and exposed to daylight for 7 days to evaporate the moisture content therein 47 . After removing the hard outer shell from the seeds, the mango kernel, which contains 70% carbohydrates, 15% fats, 5% protein, and the remaining 20% ​​calcium and phosphorus, is separated.…”
Section: Methodsmentioning
confidence: 99%
“…Then, the collected seeds are cleaned with the help of water and exposed to daylight for 7 days to evaporate the moisture content therein. 47 After removing the hard outer shell from the seeds, the mango kernel, which contains 70% carbohydrates, 15% fats, 5% protein, and the remaining 20% calcium and phosphorus, is separated. These kernels are further crushed and pressed in a local roller mill to produce Raw Mango Seed Oil (RMSO).…”
Section: Pretreatment Of Msomentioning
confidence: 99%